2021
DOI: 10.1177/1479973121993494
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and cerebral oxygenation during cycling in chronic obstructive pulmonary disease: A scoping review

Abstract: To synthesize evidence for prefrontal cortex (PFC), quadriceps, and respiratory muscle oxygenation using near-infrared spectroscopy (NIRS) during cycling in individuals with chronic obstructive pulmonary disease (COPD). A scoping review was performed searching databases (inception-August 2020): Ovid MEDLINE, EMBASE, Cochrane Systematic Reviews, Cochrane Central Register of Controlled Clinical Trials, CINAHL, SPORTDiscus and Pedro. The search focused on COPD, cycling, and NIRS outcomes. 29 studies (541 COPD par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Changes in StO 2 indicate the alteration in muscle metabolism. Studies on exercise physiology demonstrated a decline in StO 2 due to energy consumption during exercise 27 . StO 2 is also measured in patients with sepsis, which is the most common inflammatory disease requiring ICU care 7 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in StO 2 indicate the alteration in muscle metabolism. Studies on exercise physiology demonstrated a decline in StO 2 due to energy consumption during exercise 27 . StO 2 is also measured in patients with sepsis, which is the most common inflammatory disease requiring ICU care 7 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in HbT and StO 2 can reflect changes in cerebral blood volume [42] and the balance between oxygen delivery and utilization in the brain [43], respectively. The values of indices I and II for HbT and StO 2 in the high cardiopulmonary function group (≥5 METs) were higher than those in the low cardiopulmonary function group (<5 METs; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This review also points out that blood oxygen saturation may be used to control the stress caused by exercise [53,54] and also by environmental factors such as pollution [66]. Blood oxygen saturation is commonly used in the medical field to supervise patients in intensive care units and during the cardiac or pulmonary rehabilitation process [102]. This parameter provides more a profound insight into the individual's physiological reaction during exercise.…”
Section: Discussionmentioning
confidence: 99%